Cross-linkable foaming composition, foamed product obtained using the same, foaming composition and use thereof

By using hydrogenated styrene diblock copolymer and free radical initiator, cross-linked foaming technology is solved, and the problem of difficulty in obtaining high impact resilience while maintaining mechanical characteristics is achieved, and efficient and economical foaming body preparation is achieved.

CN115403891BActive Publication Date: 2025-05-09LEE CHANG YUNG CHEM IND CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202210595829.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-05-28
Filing Date
2022-05-27
Publication Date
2025-05-09
Estimated Expiration
2042-05-27

AI Technical Summary

Technical Problem

While maintaining other mechanical characteristics, existing EVA foams are difficult to obtain high impact rebound, and there is also the problem of high preparation cost.

Method used

A hydrogenated styrene diblock copolymer is used as a crosslinkable foaming composition, and a foaming body with high impact elasticity is prepared by adding a radical starter and a foaming agent and crosslinking and foaming at a specific temperature.

Benefits of technology

The impact resilience of the foamed body is achieved without damaging other mechanical characteristics, and the preparation cost is reduced by optimizing the formulation and process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115403891B_ABST
    Figure CN115403891B_ABST
Patent Text Reader

Abstract

The present invention provides a cross-linkable foaming composition, comprising a hydrogenated styrene diblock copolymer, a free radical initiator and a foaming agent, wherein the hydrogenated styrene diblock copolymer comprises: a first block comprising a conjugated diene monomer unit; and a second block comprising a styrene unit. The hydrogenated styrene diblock copolymer comprises 10 to 60 wt% of the styrene unit, 50 mol% or more of the conjugated diene monomer unit is hydrogenated, and the weight average molecular weight of the hydrogenated styrene diblock copolymer is between 30,000 and 200,000. In addition, the present invention also provides a foam obtained by cross-linking and foaming the cross-linkable foaming composition, a foaming composition and its use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cross-linkable foaming composition, a foamed body obtained by cross-linking and foaming the cross-linkable foaming composition, a foaming composition and uses thereof. Background Art

[0002] Ethylene copolymers, such as ethylene vinyl acetate (EVA), are widely used in footwear applications to make foamed products, particularly foamed sole components, which process involves adding a peroxide initiator and a chemical blowing agent at a temperature of about 120°C or less, followed by molding in a mold for crosslinking the foaming composition, and then foaming at a temperature of about 140°C to 190°C. Ethylene α-olefin copolymers are also used in footwear foam applications. For example, U.S. Pat. No. 5,407,965 discloses crosslinking a substantially linear ethylene copolymer composition for use in a foam. U.S. Pat. No. 7,666,918 B2 discloses a foaming composition and foam comprising a multi-block ethylene / α-olefin interpolymer of soft and hard segments. Mixtures of ethylene copolymers can also be used to prepare lightweight foams to balance foam properties.

[0003] Thermoplastic elastomers (TPE), such as thermoplastic polyurethane (TPU) and polyether block amide (PEBAX), are another class of materials suitable for producing lightweight foams (e.g., footwear foams). TPE is similar to thermosetting rubber, but can be melt processed like thermoplastics. It consists of two phases: a soft phase that provides elasticity and a hard phase that aggregates to form a physical crosslinked network. The TPE of the selected composition may have an inherent melt strength for foaming without crosslinking, and the resulting foam has ideal foaming properties. In general, TPE materials such as thermoplastic polyurethane cannot be made into foams in existing foaming processes for making EVA foams. For example, EP3259306A1 discloses a method for producing foamed thermoplastic polyurethane particles, comprising injecting a physical foaming agent, such as nitrogen, to foam into beaded foams.

[0004] Styrenic block copolymers (SBCs) are a class of TPEs suitable for producing lightweight foams in conventional footwear foaming processes. To produce SBC-based foams, peroxide crosslinking is required to obtain melt strength for foaming. SBCs, which have a glass transition temperature of about 100°C, can be processed at temperatures below 120°C in combination with peroxides and chemical blowing agents, and the chemical structure of the soft blocks (i.e., butadiene and / or isoprene) and hydrides can be crosslinked with peroxide initiators. Therefore, styrenic block copolymers, such as SBS and SEBS, have been used in footwear foams, particularly for modifying ethylene copolymers to obtain improved properties, such as impact resilience.

[0005] At present, the characteristics of EVA foams still need to be improved, for example, high impact resilience is obtained without damaging other characteristics (such as hardness). In addition, innovative foaming resins with novel foaming characteristics still need to be obtained in a more economical manner. Summary of the invention

[0006] The purpose of the present invention is twofold. The first purpose is to provide a diblock copolymer most suitable for footwear foam applications. The foam containing the styrene diblock copolymer exhibits the inherent characteristics of the styrene block copolymer material, namely, high impact resilience, and the foaming process of the foam is to introduce a free radical initiator and a foaming agent into a cross-linkable foaming composition at a temperature of about 120°C or below, and then inject the cross-linkable foaming composition including the free radical initiator and the foaming agent into a compression mold for cross-linking, wherein the cross-linking of the mold is carried out at a temperature of about 150°C to 190°C.

[0007] The second objective is to develop a technique for modifying the properties of ethylene copolymer foams such as EVA to achieve high impact resilience while maintaining other mechanical properties.

[0008] While not wishing to be bound by theory, the present invention is based on the discovery that hydrogenated styrene diblock copolymers are best suited for achieving the objectives of the present invention as described above.

[0009] In general practice, SBC is a diblock copolymer of a styrene hard block and a soft block such as butadiene or isoprene prepared by anionic polymerization, and then a linear ABA type or star multiblock copolymer is formed by coupling or continuous polymerization. Hydrogenated SBCs such as SEBS further improve mechanical properties and weather resistance. SBC block copolymers are widely used in many applications including footwear foam as a type of TPE. Hydrogenated SBCs, such as hydrogenated SEBS, are preferably used in footwear foam applications.

[0010] In AB-type styrene diblock copolymers, the styrene hard blocks do not bundle to form physical crosslinks like multiblock copolymers. It does not have the properties of thermoplastic elastomers, such as elasticity. In short, styrene diblock copolymers are not considered thermoplastic elastomers and their commercial uses are limited. For example, few commercial products of styrene diblock copolymers are available from global SBC manufacturers. Styrene diblock copolymers are most commonly used in adhesives, coatings, or modifiers where mechanical strength and elasticity are not of paramount importance. Unexpectedly and surprisingly, AB-type styrene diblock copolymers are very suitable for footwear foams because it is not a TPE and has significant advantages over multiblock copolymers in terms of peroxide curing, foaming mixing process, compatibility with other resins, etc. The benefits of using styrene diblock copolymers for footwear foams are further explained below.

[0011] In order to make footwear foam, SBC such as SEBS needs to be crosslinked, which is mainly crosslinked by free radical initiators to improve the melt strength of the foam. In other words, chemical crosslinking by peroxide crosslinking is introduced into the pre-existing physical crosslinking of SEBS. The SEBS structure, with styrene hard blocks capping both ends of the soft block, presents ideal thermoplastic elastomer properties, but this structure actually makes crosslinking of the middle block more difficult. In other words, the structural constraints caused by the capped styrene hard blocks make crosslinking of the butadiene middle soft block more difficult. After the middle block is crosslinked at high temperature, such as 160°C to 180°C, the reformation of the SBC microphase morphology from the melt is also constrained by the newly introduced chemical crosslinking.

[0012] On the other hand, styrene diblock copolymers do not have a pre-existing physical crosslinking network. Therefore, in the peroxide curing of styrene diblock copolymers, newly formed crosslinks are formed by peroxide crosslinking without the constraints of the shape structure of the triblock copolymer. Studies have found that styrene diblock copolymers after peroxide crosslinking are transformed into three-dimensional network block copolymers with enhanced mechanical properties and optimized foaming melt strength. Only after peroxide crosslinking, the loose styrene blocks of the diblock are connected into a network. The crosslinking results show that the peroxide crosslinking of the diblock is not only used to form chemical crosslinks by peroxide crosslinking, but also to form a physical crosslinking network.

[0013] One or more steps in making footwear foam include adding a peroxide and a blowing agent, and then injecting the mixed sample into a mold for foaming, wherein the processing temperature is controlled to a temperature that does not cause premature decomposition of the peroxide and the blowing agent. For most peroxides (e.g., dicumyl peroxide (DCP) and bis(1-(tert-butylperoxy)-1-methylethyl)-benzene (BIPB)) and blowing agents (e.g., azodicarbonamide) used to make footwear foam, the upper temperature limit for mixing is about 120°C. The glass transition temperature (Tg) of the styrene hard block is about 100°C, resulting in a narrow processing window for SEBS. In addition, due to the high shear dilution melt rheology of TPE, multi-block copolymers generally have high melt viscosity at a temperature of about 120°C. Therefore, hydrogenated SEBS can be used to make footwear foams, and the choice of SEBS is mainly limited to samples with low weight average molecular weight (Mw) and low styrene content.

[0014] Surprisingly, it has been found that styrene diblock copolymers can be readily mixed at temperatures that do not cause decomposition of the peroxide and blowing agent, an important feature in the production of footwear foams.

[0015] In addition, styrene diblock copolymers can have excellent compatibility with other ethylene copolymers (such as EVA). It is known that AB type diblocks have better self-assembly ability, which comes from the thermodynamic incompatibility between the AB blocks of the copolymer. This is also the reason why AB diblock copolymers are often used as compatibilizers for two different polymers.

[0016] According to the purpose of the present invention, the present invention provides a cross-linkable foaming composition as described below, a foam obtained by cross-linking and foaming the composition, and a preparation method thereof.

[0017] The present invention provides a cross-linkable foaming composition, comprising a hydrogenated styrene diblock copolymer, a free radical initiator and a foaming agent. The hydrogenated styrene diblock copolymer comprises: a first block comprising a conjugated diene monomer unit; and a second block comprising a styrene unit. The hydrogenated styrene diblock copolymer comprises 10 to 60 wt% of styrene units, 50 mol% or more of the conjugated diene monomer units are hydrogenated, and the weight average molecular weight of the hydrogenated styrene diblock copolymer is between 30,000 and 200,000. The present invention also provides a foam or footwear component obtained by cross-linking and foaming the cross-linkable foaming composition. Therefore, the obtained foam or footwear component comprises the hydrogenated styrene diblock copolymer and has the characteristics of the hydrogenated styrene diblock copolymer.

[0018] The present invention also provides another cross-linkable foaming composition, comprising a hydrogenated styrene diblock copolymer, an ethylene copolymer, a free radical initiator and a foaming agent. The characteristics of the hydrogenated styrene diblock copolymer are as described above and are not repeated here. In addition, the weight ratio of the ethylene copolymer to the hydrogenated styrene diblock copolymer is between 50 / 50 and 95 / 5. The present invention also provides a foam or footwear component obtained by cross-linking and foaming the above-mentioned cross-linkable foaming composition. Therefore, the obtained foam or footwear component comprises a hydrogenated styrene diblock copolymer and an ethylene copolymer, and has the characteristics of the above-mentioned hydrogenated styrene diblock copolymer and the weight ratio of the ethylene copolymer to the hydrogenated styrene diblock copolymer.

[0019] The present invention also provides a foaming composition, comprising a hydrogenated styrene diblock copolymer. The characteristics of the hydrogenated styrene diblock copolymer are as described above and will not be repeated. In addition, the present invention also provides the use of the above composition for preparing a foam.

[0020] The details of one or more embodiments of the invention are set forth in the following description. Other features, objects, and advantages of the invention will be apparent from the description and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Photograph of a sample forming a ribbon on a rotating roller to assess mixing ability. DETAILED DESCRIPTION

[0022] The following provides different embodiments of the present invention. These embodiments are used to illustrate the technical content of the present invention, but are not used to limit the scope of the present invention. A feature of an embodiment can be applied to other embodiments through appropriate modification, replacement, combination, and separation.

[0023] It should be noted that, in this document, unless otherwise specified, "having" a component is not limited to having a single component, but may have one or more components.

[0024] In this document, unless otherwise specified, the so-called feature A "or" or "and / or" feature B means that A exists alone, B exists alone, or A and B exist at the same time; the so-called feature A "and" or "and" or "and" feature B means that A and B exist at the same time; the so-called "include", "comprising", "having" and "containing" mean "including but not limited to".

[0025] As used herein and unless otherwise specified, the term "about" or "approximately" means an acceptable error of a particular value determined by a person skilled in the art, which depends in part on the way the value is measured or determined. In certain embodiments, the term "about" or "approximately" means within 1, 2, 3 or 4 standard deviations. In certain embodiments, the terms "about" and "approximately" mean within ± 20% of a given value or range, within ± 15%, within ± 10%, within ± 9%, within ± 8%, within ± 7%, within ± 6%, within ± 5%, within ± 4%, within ± 3%, within ± 2%, within ± 1%, within ± 0.5%, within ± 0.05% or lower. The quantity given here is an approximate quantity, that is, in the absence of a specific description of "about", "approximately", "substantially", "substantially", "substantially", the meaning of "about", "approximately", "substantially", "substantially" can still be implied. In addition, the phrases “ranging from a first value to a second value” and “ranging between a first value and a second value” mean that the range includes the first value, the second value and other values ​​therebetween.

[0026] Furthermore, features of different embodiments of the present invention may be combined with one another to form another embodiment.

[0027] In some embodiments, the cross-linkable foaming composition may include a hydrogenated styrene diblock copolymer, a free radical initiator, and a foaming agent. The hydrogenated styrene diblock copolymer may include: a first block including a conjugated diene monomer unit; and a second block including a styrene unit. The hydrogenated styrene diblock copolymer may include 10 to 60 wt% of styrene units, 50 mol% or more of the conjugated diene monomer units may be hydrogenated, and the weight average molecular weight of the hydrogenated styrene diblock copolymer may be between 30,000 and 200,000.

[0028] In some embodiments, the cross-linkable foaming composition may include a hydrogenated styrene diblock copolymer, an ethylene copolymer, a free radical initiator and a blowing agent. The characteristics of the hydrogenated styrene diblock copolymer are as described above and are not repeated here. In addition, the weight ratio of the ethylene copolymer to the hydrogenated styrene diblock copolymer may be between 50 / 50 and 95 / 5.

[0029] In some embodiments, a foamed body is provided which is obtained by cross-linking and foaming any of the aforementioned cross-linkable foaming compositions.

[0030] In some embodiments, a footwear component is provided which is obtained by cross-linking and foaming any of the aforementioned cross-linkable foaming compositions.

[0031] In some embodiments, the foaming composition may include a hydrogenated styrene diblock copolymer. The characteristics of the hydrogenated styrene diblock copolymer are as described above and will not be repeated herein.

[0032] In some embodiments, the foaming composition is used to prepare a foam.

[0033] Next, the components of the cross-linkable foaming composition, the foam or footwear component obtained by cross-linking and foaming the cross-linkable foaming composition, and the preparation method thereof will be described in detail. In addition, the components of the foaming composition are also described in detail.

[0034] Hydrogenated styrene diblock copolymer

[0035] The hydrogenated styrene diblock copolymer of the present invention is a diblock copolymer including a first block comprising a conjugated diene monomer unit and a second block comprising a styrene unit.

[0036] In some embodiments, the hydrogenated styrene diblock copolymer may contain about 10 to 60 wt% of styrene units based on the total weight of the hydrogenated styrene diblock copolymer. When the crosslinked foamed body is prepared with a crosslinkable foaming composition containing more than 60 wt% of styrene units, the compression set rate or impact resilience of the obtained crosslinked foamed body is poor. When the crosslinked foamed body is prepared with a crosslinkable foaming composition containing less than 10 wt% of styrene units, the mechanical properties (e.g., tensile strength) of the obtained crosslinked foamed body are poor.

[0037] In some embodiments, in order to obtain a cross-linked foam having balanced mechanical properties, the hydrogenated styrene diblock copolymer may include about 10 to 50 wt% of styrene units, based on the total weight of the hydrogenated styrene diblock copolymer, and the remainder of the hydrogenated styrene diblock copolymer is conjugated diene monomer units. Within this range, the cross-linked foam is expected to have balanced mechanical properties. In some embodiments, the hydrogenated styrene diblock copolymer may include about, for example, 10 to 55 wt%, 15 to 55 wt%, 15 to 50 wt%, 18 to 50 wt%, 18 to 45 wt%, 18 to 40 wt%, 18 to 35 wt%, or 18 to 33 wt% of styrene units, and the remainder of the hydrogenated styrene diblock copolymer is conjugated diene monomer units.

[0038] In some embodiments, the weight average molecular weight of the hydrogenated styrene diblock copolymer may be about 30,000 to 200,000. If the weight average molecular weight of the hydrogenated styrene diblock copolymer is less than 30,000, the hydrogenated styrene diblock copolymer may result in poor mechanical properties of the obtained foam. If the weight average molecular weight of the hydrogenated styrene diblock copolymer exceeds 200,000, it is difficult to process the hydrogenated styrene diblock copolymer.

[0039] In some embodiments, the weight average molecular weight of the hydrogenated styrene diblock copolymer may be about, for example, 40,000 to 200,000, 40,000 to 190,000, 50,000 to 190,000, 50,000 to 180,000, 60,000 to 180,000, 60,000 to 170,000, 60,000 to 160,000, 60,000 to 190,000, 50,000 to 180,000, 60,000 to 180,000, 60,000 to 170,000, 60,000 to 160,000, 60,000 to 18 ... 150,000, 60,000 to 140,000, 60,000 to 130,000, 60,000 to 120,000, 60,000 to 110,000, 60,000 to 100,000, 60,000 to 90,000, 65,000 to 90,000, 65,000 to 85,000, 70,000 to 85,000 or 70,000 to 80,000.

[0040] In some embodiments, the conjugated diene monomer units contained in the hydrogenated styrene diblock copolymer are not particularly limited, and known conjugated diene monomers can be used. In some embodiments, the first block can be a polymer block of a butadiene unit, an isoprene unit, or a mixture thereof. In some embodiments, the first block can be a polymer block of a butadiene unit. In some embodiments, the first block can be a polymer block of an isoprene unit. In some embodiments, the first block can be a polymer block of a butadiene unit and an isoprene unit.

[0041] In some embodiments, the second block may be a polymer block of a styrene unit. In some embodiments, the second block may be a polymer block of a styrene unit and a conjugated diene monomer unit, wherein the conjugated diene monomer unit may be a butadiene unit, an isoprene unit or a mixture thereof, and the content of the conjugated diene monomer unit is less than or equal to 15 wt % of the total weight of the second block. In some embodiments, the content of the conjugated diene monomer unit may be in the range of about 0.5 to 15 wt %, 0.5 to 14 wt %, 0.5 to 13 wt %, 0.5 to 12 wt %, 0.5 to 11 wt % or 0.5 to 10 wt % of the total weight of the second block.

[0042] In some embodiments, the first block may be a polymer block of butadiene units, isoprene units or a mixture thereof, and the second block may be a polymer block of styrene units.

[0043] In some embodiments, the first block may be a polymer block of a butadiene unit, an isoprene unit or a mixture thereof, and the second block may be a polymer block of a styrene unit and a conjugated diene monomer unit, wherein the conjugated diene monomer unit may be a butadiene unit, an isoprene unit or a mixture thereof, and the content of the conjugated diene monomer unit in the second block may account for less than or equal to 15 wt % of the total weight of the second block.

[0044] In some embodiments, the first block may be a polymer block of butadiene units, and the second block may be a polymer block of styrene units.

[0045] In some embodiments, the first block may be a polymer block of a butadiene unit, and the second block may be a polymer block of a styrene unit and a butadiene unit, wherein the content of the butadiene unit in the second block may account for less than or equal to 15 wt % of the total weight of the second block.

[0046] In some embodiments, the first block may be a polymer block of isoprene units, and the second block may be a polymer block of styrene units.

[0047] In some embodiments, the first block may be a polymer block of a butadiene unit and an isoprene unit, and the second block may be a polymer block of a styrene unit.

[0048] In some embodiments, for example, when the first block and / or the second block includes butadiene units, the 1,2-vinyl bond content of the conjugated diene monomer unit (i.e., butadiene) before hydrogenation may be between 5 and 60 mol%. If the 1,2-vinyl bond content in the conjugated diene monomer unit is less than 5 mol% or greater than 60 mol%, the compression set or impact resilience of the cross-linked foam is poor.

[0049] In some embodiments, before hydrogenation, the 1,2-vinyl bond content of the conjugated diene monomer units may be about, for example, 5 to 55 mol%, 5 to 50 mol%, 10 to 50 mol%, 15 to 50 mol%, 20 to 50 mol%, 25 to 50 mol%, 30 to 50 mol%, 35 to 50 mol% or 35 to 45 mol%.

[0050] In some embodiments, for example, when the first block and / or the second block includes isoprene units, the 3,4-vinyl bond content of the conjugated diene monomer units (i.e., isoprene) before hydrogenation may be between about 5 and 40 mol%. In some embodiments, the 3,4-vinyl bond content of the conjugated diene monomer units (i.e., isoprene) before hydrogenation may be between about, for example, 5 to 35 mol%, 5 to 30 mol%, 5 to 25 mol%, 5 to 20 mol%, or 5 to 15 mol%.

[0051] In some embodiments, after hydrogenation, about 50 mol% or more of the conjugated diene monomer units in the styrene diblock copolymer are hydrogenated. In some embodiments, after hydrogenation, about 50 to 95 mol% of the conjugated diene monomer units are hydrogenated. In some embodiments, after hydrogenation, for example, about 55 to 95 mol%, 60 to 95 mol%, 60 to 90 mol%, 65 to 90 mol%, or 70 to 90 mol% of the conjugated diene monomer units are hydrogenated. If the hydrogenation degree is too low, the styrene diblock copolymer is not easy to crosslink with the ethylene copolymer.

[0052] Here, the degree of hydrogenation refers to the total degree of hydrogenation of the conjugated diene monomer units in the hydrogenated styrene diblock copolymer. For example, in the case where the first block is a polymer block of butadiene and / or isoprene and the second block is a polymer block of styrene, the degree of hydrogenation refers to the degree of hydrogenation of the polymer of butadiene and / or isoprene. In the case where the first block is a polymer block of butadiene and / or isoprene and the second block is a polymer block of styrene and butadiene and / or isoprene, the degree of hydrogenation refers to the total degree of hydrogenation of the butadiene and / or isoprene monomer units in the polymer block of butadiene and / or isoprene and the polymer block of styrene and butadiene and / or isoprene.

[0053] The method for preparing the styrene diblock copolymer before hydrogenation is not particularly limited, and any known method can be used. In the polymerization method, living anionic polymerization can be used, carried out in a hydrocarbon solvent, and the reaction is initiated by an organic alkali metal compound. For example, the above polymer synthesis steps are clearly described in U.S. Patent No. 3,823,203. The hydrocarbon solvent is not particularly limited, and any known solvent can be used. For example, the hydrocarbon solvent can include aliphatic hydrocarbons such as n-hexane; alicyclic hydrocarbons such as cyclohexane; aromatic hydrocarbons such as xylene. The above hydrocarbon solvents can be used alone or in combination of two or more.

[0054] The initiator is not particularly limited, and any initiator known to have anionic polymerization activity for vinyl aromatic monomers (e.g., styrene) and conjugated diene monomers (e.g., butadiene) can be used, for example, aliphatic hydrocarbon alkali metal compounds, aromatic hydrocarbon alkali metal compounds, and organic amino alkali metal compounds. The alkali metal used as the initiator may include lithium, sodium, and potassium. In some embodiments, the initiator may be an aliphatic hydrocarbon alkali metal, such as n-butyl lithium.

[0055] The polymerization process for preparing the styrene diblock copolymer can be carried out similarly to those methods used for anionic polymerization. The polymerization reaction can be carried out at a temperature of about 0°C to about 180°C, more preferably about 30°C to about 150°C, and most preferably about 30°C to about 90°C. The polymerization reaction is carried out in an inert atmosphere, preferably in nitrogen, and can also be carried out at a pressure in the range of about 0.5 to about 10 bar. The polymerization process generally takes less than 12 hours, depending on the temperature, the concentration of the monomer components, the polymer molecular weight, etc.

[0056] The hydrogenation of the styrene diblock copolymers can be carried out using known hydrogenation methods. For example, methods such as those described in U.S. Pat. Nos. 3,595,942 and 3,700,633 can be used. These hydrogenation methods use suitable catalysts. The catalysts mentioned can contain metals of Group VIII of the Periodic Table (e.g., nickel or cobalt) and can be used together with a suitable reducing agent, such as an alkyl aluminum or a hydride of a metal selected from Groups IA, II-A and III-B of the Periodic Table, particularly lithium, magnesium or aluminum.

[0057] The hydrogenation process is not particularly limited, and the hydrogenation is usually carried out at a temperature of 0° C. to 180° C., more preferably 30° C. to 150° C. The hydrogen pressure used in the process is not particularly limited, and is usually 0.1 to 20 MPa, 0.2 to 15 MPa, or 0.3 to 5 MPa. The reaction time is usually 1 minute to 10 hours or 10 minutes to 5 hours.

[0058] The hydrogenation process can be carried out by a batch process, a continuous process or a combination thereof. If necessary, the catalyst residue can be removed. The hydrogenated polymer can be separated by pouring into hot water while stirring, and the organic solvent can be removed by steam stripping.

[0059] In some embodiments, the microstructure of the conjugated diene segment of the hydrogenated styrene diblock copolymer, such as the vinyl bond content and styrene content before hydrogenation and the degree of hydrogenation after hydrogenation, can be measured using proton nuclear magnetic resonance (1H-NMR). In addition, the weight average molecular weight can be determined using gel permeation chromatography (GPC).

[0060] The basic synthesis method for preparing hydrogenated styrene-butadiene diblock copolymers is briefly described here, but the present invention is not limited thereto. First, cyclohexane as a solvent and n-butyl lithium as an initiator are passed into a reactor equipped with a heater and an agitator. Secondly, styrene is added to the solvent for anionic polymerization. In the third step, butadiene is added to the reactor, and the reaction mixture is further polymerized to form a styrene-butadiene diblock copolymer structure. The block copolymer is then hydrogenated in a pressure vessel using 2-ethylhexanoic acid nickel / TEAL catalyst and hydrogen. After the desired amount of butadiene block is hydrogenated, the hydrogenation reaction is terminated. The resulting sample is washed with hot acidic water to remove residual catalyst.

[0061] In addition, for the purpose of improving the properties of the foam, the hydrogenated styrene diblock copolymer can selectively contain up to 30 wt% of a hydrogenated styrene multiblock copolymer of similar composition, such as a triblock copolymer. The styrene multiblock copolymer can have a styrene content of 10 to 40 wt%, a weight average molecular weight of about 30,000 to 80,000, a 1, 2-vinyl bond content of the conjugated diene monomer unit before hydrogenation of 10 to 50 mol%, and a degree of hydrogenation of the conjugated diene monomer unit of 60 to 95 mol%. The weight ratio of the hydrogenated styrene multiblock copolymer to the hydrogenated styrene diblock copolymer is related to the foaming process and the foaming properties required for the final application.

[0062] Ethylene copolymer

[0063] In some embodiments of the present invention, the cross-linkable foaming composition may include the aforementioned hydrogenated styrene diblock copolymer and ethylene copolymer.

[0064] In some embodiments, the weight ratio of the ethylene copolymer to the hydrogenated styrene diblock copolymer may be between 50 / 50 and 95 / 5. In some embodiments, the weight ratio of the ethylene copolymer to the hydrogenated styrene diblock copolymer may be between, for example, 50 / 50 and 90 / 10, 60 / 40 and 90 / 10, 65 / 35 and 90 / 10, or 70 / 30 and 90 / 10.

[0065] In the present invention, the ethylene copolymer is not particularly limited, and known ethylene copolymers can be used. For example, suitable ethylene copolymers may include polyethylene (PE), ethylene-vinyl acetate copolymers (EVA) obtained by copolymerization of ethylene and vinyl acetate, ethylene-α-olefin copolymers obtained by random or block copolymerization of ethylene and C3-10 α-olefins, or combinations thereof.

[0066] In some embodiments, the ethylene copolymer may be polyethylene, which may be high-density polyethylene, low-density polyethylene, or a combination thereof.

[0067] In some embodiments, the ethylene copolymer may be an ethylene-vinyl acetate copolymer, and the content of vinyl acetate is about 15 to 40 wt % based on the total weight of the ethylene copolymer. In some embodiments, the content of vinyl acetate is about 15 to 35 wt %, 15 to 30 wt %, 18 to 30 wt %, or 20 to 30 wt % based on the total weight of the ethylene copolymer.

[0068] In some embodiments, the ethylene copolymer may be an ethylene-α-olefin copolymer, wherein the α-olefin may include 1-butene, 1-pentene, 1-hexene, 1-octene, the like, or a combination thereof.

[0069] Free Radical Initiators

[0070] In some embodiments of the present invention, the cross-linkable foaming composition may further include a free radical initiator. The free radical initiator used to cross-link the cross-linkable foaming composition is not particularly limited, and any known free radical initiator may be used.

[0071] In some embodiments, the free radical initiator may be an organic peroxide.

[0072] In some embodiments, the organic peroxide may be selected from the group consisting of dicumyl peroxide, 2,5-dimethyl-2,5-di-(t-butyl peroxy)hexane, bis(1-(tert-butylperoxy)-1-methylethyl)-benzene, and combinations thereof. In some embodiments, the organic peroxide may be bis(1-(tert-butylperoxy)-1-methylethyl)-benzene. However, the present invention is not limited thereto.

[0073] The amount of the free radical initiator is not particularly limited. In some embodiments, based on the total weight of the cross-linkable foaming composition, the amount of the free radical initiator can be about 0.01 to 10 wt%, 0.01 to 9 wt%, 0.01 to 8 wt%, 0.01 to 7 wt%, 0.01 to 6 wt%, 0.01 to 5 wt%, 0.01 to 4 wt%, 0.05 to 4 wt%, 0.05 to 3 wt%, 0.1 to 3 wt%, 0.1 to 2.5 wt%, 0.1 to 2 wt%, 0.1 to 1.5 wt% or 0.1 to 1 wt%.

[0074] Foaming agent

[0075] In some embodiments of the present invention, the cross-linkable foaming composition may further include a foaming agent. The foaming agent is not particularly limited, and any known foaming agent may be used. For example, the foaming agent may be a chemical foaming agent, a physical foaming agent, or a combination thereof.

[0076] In some embodiments, the foaming agent is a chemical foaming agent.

[0077] In some embodiments, the blowing agent may include an organic blowing agent, such as azodicarbonamide (ADCA), bis(1-(tert-butylperoxy)-1-methylethyl)-benzene, 4,4'-oxybis(benzenesulfonylhydrazide), p-toluenesulfonylsemicarbazide, N, N'-dinitrosopentamethylenetetramine, diphenylsulfone-3,3'-disulfonyl hydrazide (DPSDSH), trihydraznotriazine, or a combination thereof; or an inorganic thermally decomposable blowing agent, such as sodium bicarbonate, ammonium bicarbonate, sodium carbonate, ammonium carbonate, or a combination thereof. Among them, the organic foaming agent and the inorganic thermal decomposition foaming agent can be used alone or in combination. In some embodiments, the foaming agent can be azodicarbonamide. However, the present invention is not limited thereto.

[0078] The amount of the foaming agent is not particularly limited. In some embodiments, the amount of the foaming agent can be about 0.5 to 10 wt%, 0.5 to 9 wt%, 0.5 to 8 wt%, 0.5 to 7 wt%, 0.5 to 6 wt%, 0.5 to 5 wt% or 1 to 5 wt% based on the total weight of the cross-linkable foaming composition.

[0079] In some embodiments, the blowing agent may be a physical blowing agent, such as nitrogen, carbon dioxide, alkanes, cycloalkanes, dialkyl ethers, cycloalkylene ethers, fluoroalkanes, hydrofluoroolefins, hydrochlorofluoroolefins, or combinations thereof.

[0080] Other additives

[0081] In some embodiments of the present invention, if necessary, in addition to the aforementioned components, the cross-linkable foaming composition may further selectively include other additives, such as a cross-linking aid, an organic metal compound, a filler, a heat stabilizer, a weathering stabilizer, a pigment, etc. However, the present invention is not limited thereto.

[0082] In some embodiments of the present invention, in order to accelerate the rate of the cross-linking reaction, the cross-linkable foaming composition may further include a cross-linking aid. For example, the cross-linking aid may include, but is not limited to, triallylisocyanurate, triallyl cyanurate, ethylene glycol dimethacrylate, vinyl butyrate, etc.

[0083] In some embodiments of the present invention, in order to make the cross-linked foam body more fine or more uniform in pores, the cross-linked foam composition may further include an organic metal compound. For example, the organic metal compound may include, but is not limited to, zinc diacrylate or zinc dimethacrylate, which may also serve as a cross-linking aid.

[0084] In some embodiments of the present invention, in order to save costs, adjust hardness, modulus or nucleation, the cross-linkable foaming composition may further include a filler. For example, the filler may include, but is not limited to, clay, silicon dioxide, talc, titanium dioxide, zinc oxide, calcium carbonate, etc.

[0085] In some embodiments of the present invention, in order to increase the durability of the foam product, the cross-linkable foam composition may further include a heat stabilizer, a weather stabilizer or a combination thereof. For example, the heat stabilizer may include, but is not limited to, a phosphorus-based heat stabilizer such as Irgafos 168. For example, the weather stabilizer may include, but is not limited to, a hindered phenol weather stabilizer such as pentaerythritol tetrakis[3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate]

[0086] In some embodiments of the present invention, the cross-linkable foaming composition may further include a pigment. For example, the pigment may include, but is not limited to, azo pigments, phthalocyanine pigments, oxide pigments, chromate pigments, molybdate pigments, inorganic pigments or carbon black.

[0087] Preparation of cross-linkable foaming composition

[0088] The crosslinkable foaming composition of the present invention can be prepared by first melt-blending the hydrogenated styrene diblock copolymer, ethylene copolymer or a combination thereof using a kneader, and then adding a free radical initiator and a foaming agent, and other additives (such as a filler) can be added. Before adding the free radical initiator and the foaming agent, the temperature is below 120° C. to avoid premature decomposition of the free radical initiator or the foaming agent.

[0089] The method of melt blending is not particularly limited, and known methods can be used. For example, extrusion devices such as single-screw extruders, twin-screw extruders, multi-screw extruders, Henschel mixers, Banbury mixers, roll mills, and kneaders can be used in the present invention. In some embodiments, melt blending is performed using a kneader.

[0090] After the step of melt blending, the shape of the crosslinkable foaming composition of the present invention is not particularly limited. For example, it can be formed into particles, sheets, strips, discs, etc. For example, the components can be mixed and formed into particles by a granulator or similar machine. For example, after kneading the components of the composition, a roll mill is used to form a sheet. Thus, an uncrosslinked and unfoamed expandable sheet can be produced, wherein the expandable sheet comprises any of the aforementioned crosslinkable foaming compositions.

[0091] Preparation of cross-linked foam

[0092] The cross-linkable foaming composition provided by the present invention can be cross-linked and foamed to obtain the foam of the present invention.

[0093] The cross-linking foaming method is not particularly limited and may be any known method. Here, an example of foaming the cross-linkable foaming composition of the present invention by pressing the cross-linkable foaming composition into a sheet is provided. The cross-linking foaming sheet is cut into a size of 1.0 to 1.2 times the volume of the mold and placed in the mold. In a typical foaming molding operation, the mold is maintained at about 150 to 200°C and the mold clamping pressure is 30 to 300 kgf / cm 2 , the holding time is 3 to 50 minutes. In the mold, while the crosslinking reaction is carried out, the foaming agent is also decomposed. After waiting for the holding time, the mold is opened, and the crosslinkable foaming composition is made into a crosslinked foam body. In the industrial production of the foam body, an injection molding process can be adopted in which the crosslinkable foaming composition is melt-injected into the mold for crosslinking foaming.

[0094] The specific gravity (also referred to as density) of the cross-linked foam obtained from the cross-linkable foam composition may be about 0.05 to 0.5 g / cm 3 , for example, 0.05 to 0.45 g / cm 3 , 0.05 to 0.4 g / cm3 , 0.1 to 0.4 g / cm 3 , 0.1 to 0.35 g / cm 3 , 0.1 to 0.3 g / cm 3 or 0.1 to 0.25 g / cm 3 However, the present invention is not limited thereto, and the specific gravity of the foam can be adjusted by changing the ingredients of the cross-linkable foaming composition.

[0095] The impact resilience of the cross-linked foamed body obtained by the cross-linkable foaming composition can be about 40 to 80%. In some embodiments, when the foam is formed by the cross-linkable foaming composition including hydrogenated styrene diblock copolymer, the impact resilience of the foam can be about 40 to 80%, 45 to 80%, 50 to 80% or 55 to 80%. In some embodiments, when the foam is formed by the cross-linkable foaming composition including hydrogenated styrene diblock copolymer and ethylene copolymer, the impact resilience of the foam can be about 40 to 80%, 45 to 80% or 50 to 80%. However, the present invention is not limited to this, and the impact resilience of the foam can be adjusted by changing the composition of the cross-linkable foaming composition.

[0096] The hardness (Asker C) of the crosslinked foam obtained from the crosslinkable foaming composition may be about 20 to 80. In some embodiments, when the foam is formed from the crosslinkable foaming composition including the hydrogenated styrene diblock copolymer, the hardness (Asker C) of the foam may be about, for example, 20 to 80, 20 to 75, 20 to 70, 20 to 65, 20 to 60, 20 to 55, 20 to 50, 20 to 45 or 20 to 40. In some embodiments, when the foam is formed from the crosslinkable foaming composition including the hydrogenated styrene diblock copolymer and the ethylene copolymer, the hardness (Asker C) of the foam may be about, for example, 20 to 80, 20 to 75, 20 to 70, 25 to 70, 30 to 70, 30 to 65, 30 to 60 or 30 to 55. However, the present invention is not limited thereto, and the hardness (Asker C) of the foam may be adjusted by changing the ingredients of the crosslinkable foaming composition.

[0097] The compression set of the cross-linked foam obtained from the cross-linkable foam composition may be about 30 to 65%, such as 35 to 65% or 40 to 65%. However, the present invention is not limited thereto, and the compression set of the foam may be adjusted by changing the ingredients of the cross-linkable foam composition.

[0098] The foam obtained from the crosslinkable foam composition of the present invention has excellent balanced mechanical properties, at least in terms of impact resilience, light weight, compression set rate and tearing properties. Therefore, the foam obtained from the crosslinkable foam composition of the present invention can be used as a lightweight and flexible material and can be widely used in automobiles, buildings, daily necessities and sporting goods.

[0099] In some embodiments, the cross-linked foam obtained from the cross-linkable foaming composition of the present invention can be used as a footwear component, such as a shoe midsole.

[0100] In particular, when the foaming specific gravity decreases, the mechanical properties tend to decrease; however, in the present invention, it is expected to produce a lightweight cross-linked foam with balanced mechanical properties, which is particularly suitable for shoe midsoles or sports foam pads.

[0101] Therefore, in some embodiments, the foam obtained by cross-linking and foaming the cross-linkable foaming composition of the present invention can be used as a footwear component, such as a midsole or a sports foam pad, but the present invention is not limited thereto.

[0102] Example

[0103] The present embodiment will be described in detail below with reference to the examples. However, the present embodiment is not limited to these examples. In the examples and comparative examples, the preparation and identification of the compositions used in the examples and comparative examples and the evaluation of the mechanical properties of the cross-linked foams can be carried out by the following methods.

[0104] The polymer structure of the hydrogenated styrene diblock copolymer is determined as follows.

[0105] Molecular weight and molecular weight distribution

[0106] The weight average molecular weight (Mw) and number average molecular weight (Mn) are tested and determined using gel permeation chromatography (GPC) equipment. The molecular weight values ​​of the peaks in the chromatogram are calculated using a calibration curve of commercially available standard polystyrene. The molecular weight distribution (Mw / Mn) is determined based on the weight average molecular weight (Mw) and number average molecular weight (Mn). More detailed information on the test procedures and instrument information is described below. The instrument is a commercial GPC system provided by Waters, including a PDI and a refractive index detector. Tetrahydrofuran (THF) is usually selected as the solvent. The measurement temperature is maintained at 40°C. The flow rate is 1 ml / min and the injection volume is 100 μl. The ratio of hydrogenated block copolymer / THF is 3 mg / 15cc.

[0107] Styrene content and vinyl bond content

[0108] Before hydrogenation, the styrene content and vinyl bond content of the hydrogenated styrene diblock copolymer can be measured using a 1H-NMR spectrometer, VARIAN 400, provided by Agilent Technologies, Inc. Generally, deuterated chloroform is selected as the solvent.

[0109] Degree of hydrogenation

[0110] The degree of hydrogenation can be calculated from the reduction rate of the unsaturated bond signal in the 1H-NMR spectrum as follows.

[0111] Degree of hydrogenation (mol%) = B / (A+B) x 100%

[0112] A: Number of moles of unhydrogenated conjugated diene monomer units

[0113] B: Number of moles of hydrogenated conjugated diene monomer units

[0114] Melt flow index

[0115] The melt flow index (MFI) can be measured according to ASTM-D1238.

[0116] The novel status of the styrene diblock copolymers was evaluated as follows.

[0117] Compounding capability

[0118] The mixing ability of the styrene diblock samples of the examples and comparative examples was evaluated at a temperature not exceeding 120°C using an open roll mixer (HT-8807) provided by Hongda Instrument Co., Ltd. This is to simulate the shoe material mixing process, which includes adding a free radical initiator and a chemical foaming agent, and then injecting the mixture into a foaming stamping die at a temperature that does not cause premature decomposition. The temperature that does not cause the free radical initiator and the foaming agent to decompose is 100 to 120°C.

[0119] Before the mixing process, the rollers are heated to 120°C. Then, the sample is placed between the two rollers of the drum mixer. The material is ground into small pieces and gradually melted to form a ribbon. After the material changes from a solid state to a molten state, the molten polymer forms a uniform ribbon attached to the rotating rollers. At this point, the degree of mixing difficulty and the quality of the ribbon can be observed and determined. If the sample does not melt well under this temperature condition, the melted surface will be uneven. At the same time, small holes of irregular size can also be observed. On the other hand, if the sample can melt well under this temperature condition, the melted surface will be smooth and uniform.

[0120] The band formation on the roll surface was rated on a scale of 1 to 5, with a rating of 5 indicating a perfect molten film formation and a rating of 1 indicating a poor film formation. In addition, photographs of the band formed on the roll were taken for visual comparison.

[0121] Resin tensile properties

[0122] The tensile properties of crosslinked and non-crosslinked samples were measured according to ASTM D412. Dumbbell-shaped test specimens with a thickness of 2 mm, a length of 115 mm, and a width of 25 mm were prepared by press molding the samples at 175°C for 5 minutes. To prepare the crosslinked test specimens, the samples were first mixed with BIPB peroxide at 110°C in a Brabender mixer. The mixed sample was then transferred to a mold and press molded at 175°C for 10 minutes to complete the crosslinking in the mold. The sheets were then cut into test specimens for tensile strength measurement.

[0123] MDR Testing

[0124] The crosslinking kinetics of peroxide crosslinked samples were evaluated using a moving die rheometer (MDR-A1) provided by U-CAN DYNATEX INC in accordance with ASTM D5289. The mixed material was prepared by mixing the sample and BIPB organic peroxide in a Brabender mixer at 100°C and 15 rpm for 15 minutes. The MDR test parameters were set to 100 cycles per minute and an arc of 0.5 degrees. For this measurement, the temperature of the MDR test chamber was set to 175°C. The MDR data is the minimum torque (ML), which measures the viscosity in the molten state before the crosslinking chemical reaction becomes effective, and the maximum torque (MH), which measures the viscosity of the fully crosslinked material. The difference between the maximum torque and the minimum torque (MH - ML) is the degree of crosslinking of the peroxide crosslinked sample.

[0125] The mechanical properties of the crosslinked foam were evaluated in the following manner.

[0126] proportion

[0127] The primary cross-linked foam was punched out into a circular shape having a diameter of 2.54 cm and a thickness of 1 cm, and measured by an electronic densitometer (MS-204S, manufactured by Mettler Toledo Co., Ltd.).

[0128] hardness

[0129] The hardness (Asker C) of the primary crosslinked foam was measured using an Asker C hardness meter (Type C, manufactured by Polymer Co., Ltd.) according to ASTM D2240, and the value was read within 1 second. In addition, the average value (arithmetic mean) of 5 points was taken as the hardness.

[0130] Split tear strength

[0131] The delamination tear strength of the primary crosslinked foam was measured according to ASTM D3574 F.

[0132] Tensile Strength

[0133] The tensile strength at break of the primary cross-linked foam was measured according to ASTM D412.

[0134] Elongation

[0135] The elongation at break of the primary crosslinked foam is measured according to ASTM D412.

[0136] Compression set

[0137] The primary cross-linked foam was punched into a circular shape with a diameter of 2.54 cm, used as a test piece, and compressed to a thickness of 50%. After being kept at 50°C for 6 hours, the pressure was released and the thickness was measured after 1 hour. The magnitude of the residual deformation was evaluated.

[0138] Impact Resilience

[0139] The impact resilience of the cross-linked foam is measured in a vertical rebound tester according to ASTM-D2632. The impact resilience refers to the ratio of the rebound height of a metal plunger with a specified mass and shape dropped on the foam sample to the drop height.

[0140] The resin compositions of Examples and Comparative Examples are as follows.

[0141] Styrene block copolymer

[0142] SEB-1: Hydrogenated styrene-butadiene diblock copolymer

[0143] First, 4800 g of cyclohexane, 14.1 mmol of n-butyl lithium and 166 mmol of tetrahydrofuran (THF) were placed in a 10-liter reactor equipped with a heater and a stirrer. Second, 160 g of styrene was added to the solvent and anionic polymerization was carried out at a temperature of about 45°C. In the third step, 640 g of butadiene was added to the reactor, and the reaction mixture was further polymerized to form a styrene-butadiene diblock copolymer structure, wherein the 1,2-vinyl bond content of the butadiene block was about 40 mol%.

[0144] The styrene diblock copolymer obtained through the above steps is then hydrogenated in a pressure vessel using nickel 2-ethylhexanoate / TEAL catalyst and hydrogen. The temperature of the hydrogenation process is controlled at about 40°C to 100°C. After about 80 mol% of the butadiene block is hydrogenated, the hydrogenation reaction is terminated. Then, the obtained sample is washed with hot acidic water to remove the residual catalyst. Finally, the block copolymer is separated by coagulation in hot water and then dried. The yield of the hydrogenated styrene diblock copolymer is about 80%.

[0145] After analysis, the obtained hydrogenated styrene diblock copolymer had a styrene content of 20 wt%, a hydrogenation degree of 80 mol%, a weight average molecular weight of about 60,000, a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.05, and an MFI of 3.9 measured at 190°C / 5 kgf.

[0146] SEB-2: Hydrogenated styrene-butadiene diblock copolymer

[0147] SEB-2 was prepared in the same manner as SEB-1. SEB-2 was a hydrogenated styrene-butadiene diblock copolymer having a styrene content of 20 wt%, a 1,2-vinyl bond content of about 39 mol% in the butadiene block, a degree of hydrogenation of 83.4 mol%, a weight average molecular weight of about 75,000, and a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.03.

[0148] SEB-3: Hydrogenated styrene-butadiene diblock copolymer

[0149] SEB-3 was prepared in the same manner as SEB-1. SEB-3 is a hydrogenated styrene-butadiene diblock copolymer having a styrene content of 20 wt %, a 1,2-vinyl bond content of about 40 mol % in the butadiene block, a degree of hydrogenation of 86 mol %, a weight average molecular weight of about 112,000, a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.03, and an MFI measured at 230°C / 5 kg of less than 0.1.

[0150] SEB-4: Hydrogenated styrene-butadiene diblock copolymer

[0151] SEB-4 was prepared in the same manner as SEB-1. SEB-4 is a hydrogenated styrene-butadiene diblock copolymer having a styrene content of 20 wt%, a 1,2-vinyl bond content of about 20 mol% in the butadiene block, a hydrogenation degree of 80 mol%, a weight average molecular weight of about 60,000, a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.03, and an MFI of 0.39 measured at 190°C / 5kg.

[0152] SEB-5: Hydrogenated styrene-butadiene diblock copolymer

[0153] SEB-5 was prepared in the same manner as SEB-1. SEB-5 is a hydrogenated styrene-butadiene diblock copolymer having a styrene content of 24.7 wt%, a 1,2-vinyl bond content of about 42.7 mol% in the butadiene block, a degree of hydrogenation of 80.8 mol%, a weight average molecular weight of about 60,000, a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.03, and an MFI of 4 measured at 190°C / 5 kg.

[0154] SEB-6: Hydrogenated styrene-butadiene diblock copolymer

[0155] SEB-6 was prepared in the same manner as SEB-1. SEB-6 is a hydrogenated styrene-butadiene diblock copolymer having a styrene content of 29.8 wt%, a 1,2-vinyl bond content of about 39.9 mol% in the butadiene block, a degree of hydrogenation of 87 mol%, a weight average molecular weight of about 59,000, and a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.03.

[0156] (S / EB)-EB-1: Hydrogenated (styrene / butadiene)-butadiene diblock copolymer

[0157] (S / EB)-EB-1 is a hydrogenated (styrene / butadiene)-butadiene diblock copolymer, comprising a copolymer block of styrene and butadiene, and a block of butadiene. The preparation method thereof is as follows.

[0158] First, 4800 g of cyclohexane, 11.09 mmol of n-butyl lithium and 166 mmol of tetrahydrofuran (THF) were added to a 10-liter reactor equipped with a heater and a stirrer. Secondly, 158 g of styrene and 8 g of butadiene (styrene / butadiene weight ratio of 95 / 5) were added to the reactor, and anionic copolymerization was initiated at a temperature of about 50°C until the reaction of styrene and butadiene was completed. In the third step, 667 g of butadiene was added to the reactor. After the polymerization of butadiene was completed, methanol was added to terminate the polymerization to form a (styrene / butadiene)-butadiene diblock copolymer. The 1,2-vinyl bond content in the butadiene block was about 40.8 mol%.

[0159] The hydrogenation process was the same as that for preparing SEB-1. After analysis, the obtained hydrogenated (styrene / butadiene)-butadiene diblock copolymer had a styrene content of 19.7 wt%, a hydrogenation degree of butadiene of 80 mol%, a weight average molecular weight of about 76,000, a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.04, and an MFI of 1.1 measured at 190°C / 5 kgf.

[0160] (S / EB)-EB-2: Hydrogenated (styrene / butadiene)-butadiene diblock copolymer

[0161] (S / EB)-EB-2 is a hydrogenated (styrene / butadiene)-butadiene diblock copolymer, comprising a copolymer block of styrene and butadiene, and a block of butadiene. Its preparation method is the same as that of (S / EB)-EB-1, except that in the preparation of the copolymer block of styrene and butadiene, the weight ratio of styrene / butadiene is 90 / 10. The 1,2-vinyl bond content in the butadiene block is about 43.7 mol%.

[0162] The hydrogenated (styrene / butadiene)-butadiene diblock copolymer has a styrene content of 28.5 wt%, a hydrogenation degree of butadiene of 78 mol%, a weight average molecular weight of about 75,000, a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.04, and an MFI of 2.7 measured at 190°C / 5 kgf.

[0163] SEP-1: Hydrogenated styrene-isoprene diblock copolymer

[0164] SEP-1 is a hydrogenated styrene-isoprene diblock copolymer, and its preparation and determination are described in detail below. First, 4800 g of cyclohexane, 7.06 mmol of n-butyl lithium, and 2.66 mmol of tetrahydrofuran (THF) are added to a 10-liter reactor equipped with a heater and an agitator. Secondly, 534 g of isoprene is added to the reactor to initiate anionic polymerization at a temperature of about 45°C. Thirdly, 313 g of styrene is added to the reactor, and the reaction mixture is further polymerized to prepare a styrene-isoprene diblock copolymer. The 3,4-vinyl bond content in the isoprene block is about 9.1 mol%.

[0165] The styrene-isoprene diblock copolymer obtained in the above steps is then hydrogenated in a pressure vessel using nickel 2-ethylhexanoate / TEAL catalyst and hydrogen. The temperature of the hydrogenation process is controlled at about 40°C to 100°C. After about 80 mol% of the isoprene block is hydrogenated, the hydrogenation reaction is terminated. The obtained sample is then washed with hot acidic water to remove the residual catalyst. Finally, the block copolymer is separated by coagulation in hot water and then dried. The yield of the hydrogenated styrene diblock copolymer is about 80%.

[0166] After analysis, the obtained hydrogenated styrene-isoprene diblock copolymer had a styrene content of 37 wt %, a hydrogenation degree of 80 mol %, a weight average molecular weight of about 121,000, a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.03, and an MFI of 4 measured at 230°C / 5 kgf.

[0167] SEP-2: Hydrogenated styrene-isoprene diblock copolymer

[0168] SEP-2 was prepared in the same manner as SEP-1, which is a hydrogenated styrene-isoprene diblock copolymer having a styrene content of 25 wt%, a 3,4-vinyl bond content in the isoprene block of about 9 mol%, a degree of hydrogenation of 84 mol%, a weight average molecular weight of about 118,000, a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.03, and an MFI of 2.2 measured at 230°C / 5 kgf.

[0169] EEPS-1: Hydrogenated (butadiene / isoprene)-styrene diblock copolymer

[0170] EEPS-1 is a hydrogenated (butadiene / isoprene)-styrene diblock copolymer, and its preparation and determination are described in detail below. First, 4800 g of cyclohexane, 7.89 mmol of n-butyl lithium and 2.66 mmol of tetrahydrofuran (THF) were added to a 10-liter reactor equipped with a heater and a stirrer. Secondly, 295 g of isoprene and 197 g of butadiene were added to the reactor at the same time (the I / B molar ratio was controlled at 1.25), and anionic polymerization was initiated at a temperature of about 50°C until the reaction of isoprene and butadiene was completed. In the third step, 289 g of styrene was added to the reactor. After the polymerization of styrene was completed, methanol was added to terminate the polymerization to form an (isoprene / butadiene)-styrene diblock copolymer. The 3,4-vinyl bond content in the isoprene block is about 13 mol%, while the 1.2-vinyl bond content in the butadiene block is about 16 mol%.

[0171] Then, the (butadiene / isoprene)-styrene diblock copolymer obtained by the above steps is hydrogenated in a pressure vessel using 2-ethylhexanoic acid nickel / TEAL catalyst and hydrogen. The temperature of the hydrogenation process is controlled at about 50°C to 90°C. Once the cumulative amount of absorbed hydrogen reaches the amount of the corresponding target hydrogenation degree, the hydrogenation reaction is terminated. Then, the obtained sample is washed with hot acidic water to remove the residual catalyst. Finally, the block copolymer is separated by condensation in hot water and then dried. The hydrogenation degree of the hydrogenated styrene diblock copolymer is 78.1 mol%, the styrene content is 37.1 wt%, the weight average molecular weight is about 128,000, the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.06, and the MFI measured at 230°C / 5 kgf is 0.63.

[0172] SEBS-1: Partially hydrogenated styrene-butadiene-styrene triblock copolymer

[0173] SEBS-1 is a partially hydrogenated styrene-butadiene-styrene triblock copolymer obtained from Asahi Kasei under the trade name Tuftec P1083, with a styrene content of 20 wt% and a density of 0.89 g / cm 3 , MFI at 190°C / 2.16kgf is 3.0 g / 10 minutes, and hardness (Durometer A) is 56. After analysis, the weight average molecular weight of SEBS-1 is about 61,000, and the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.04.

[0174] SEBS-2: Hydrogenated styrene-butadiene-styrene triblock copolymer

[0175] SEBS-2 is a hydrogenated styrene-butadiene-styrene triblock copolymer, and its preparation and determination are described in detail below. First, 4800 g of cyclohexane, 14.5 mmol of n-butyl lithium and 166 mmol of tetrahydrofuran (THF) were added to a 10-liter reactor equipped with a heater and a stirrer. Secondly, 100 g of styrene was added to the solvent and anionic polymerization was carried out at a temperature of about 45 ° C. In the third step, 600 g of butadiene was added to the reactor until the butadiene reaction was completed. In the fourth step, 100 g of styrene was added to the reactor, and methanol was added after the styrene polymerization was completed to terminate the polymerization and form a styrene-butadiene-styrene triblock copolymer structure. The styrene content of the styrene-butadiene-styrene triblock copolymer is 24wt%, and the 1,2-vinyl bond content of the butadiene block is about 43.4 mol%.

[0176] The hydrogenation was carried out in the same manner as that of SEB-1, and the hydrogenation degree of the hydrogenated styrene-butadiene-styrene triblock copolymer was 83.5 mol %, the weight average molecular weight was about 57,000, the molecular weight distribution (weight average molecular weight / number average molecular weight) was 1.03, and the MFI measured at 190°C / 5 kgf was 3.6.

[0177] SEPS-1: Hydrogenated styrene-isoprene-styrene triblock copolymer

[0178] SEPS-1 is a hydrogenated styrene-isoprene-styrene triblock copolymer, and its preparation and determination are described in detail below. First, 4800 g of cyclohexane, 10.2 mmol of n-butyl lithium and 2.66 mmol of tetrahydrofuran (THF) were added to a 10-liter reactor equipped with a heater and a stirrer. Secondly, 120 g of styrene was added to the solvent and anionic polymerization was carried out at a temperature of about 45 ° C. In the third step, 560 g of isoprene was added to the reactor until the isoprene reaction was completed. In the fourth step, 120 g of styrene was added to the reactor, and after the polymerization of styrene was completed, methanol was added to terminate the polymerization to form a styrene-isoprene-styrene triblock copolymer structure. The 3,4-vinyl bond content of the isoprene block of the styrene-isoprene-styrene triblock copolymer is about 10 mol%.

[0179] The hydrogenation was carried out in the same manner as that of SEP-1. The hydrogenation degree of the hydrogenated styrene-isoprene-styrene triblock copolymer was 78.8 mol%, the styrene content was 28.8 wt%, the weight average molecular weight was about 95,000, the molecular weight distribution (weight average molecular weight / number average molecular weight) was 1.03, and the MFI measured at 230°C / 5 kgf was 0.23.

[0180] Ethylene copolymer

[0181] EVA-1: Ethylene-vinyl acetate copolymer

[0182] EVA-1 is an ethylene-vinyl acetate copolymer having a vinyl acetate content of 25 wt %, an MFI of 3 g / 10 min measured at 190° C. / 2.16 kgf, and is manufactured by USI Corporation under the trade name “UE659”.

[0183] EVA-2: Ethylene-vinyl acetate copolymer

[0184] EVA-2 is an ethylene-vinyl acetate copolymer having a vinyl acetate content of 18 wt % and an MFI of 3 g / 10 min measured at 190° C. / 2.16 kgf, and is manufactured by USI Corporation under the trade name “UE629”.

[0185] POE-1: Ethylene copolymer

[0186] POE-1 is an ethylene / 1-octene copolymer with an MFI of 3.0 g / 10 min and a hardness of 0.902 g / cm2 at 190°C / 2.16 kgf. 3 , which is manufactured by The Dow Chemical Company under the trade name "Engage 8450".

[0187] POE-2: Ethylene copolymer

[0188] POE-2 is an ethylene / 1-butene copolymer with an MFI of 1.2 g / 10 min and a hardness of 0.885 g / cm2 at 190°C / 2.16 kgf. 3 , which is manufactured by Mitsui Chemicals, Inc. under the trade name "Tafmer DF810".

[0189] Organic peroxide

[0190] Bis(1-(tert-butylperoxy)-1-methylethyl)-benzene (BIPB) manufactured by Arkema Group was used.

[0191] Chemical foaming agent

[0192] Azodicarbonamide (AC) manufactured by Kumyang Corporation was used.

[0193] Other additives

[0194] Calcium carbonate (manufactured by Yuncheng Chemical Industry Co., Ltd.), ZnO (zinc oxide, manufactured by Diamonchem International Co., Ltd.), and stearic acid (manufactured by Vulchem ​​Inc.) were used.

[0195] result

[0196] Table 1 below lists polymer structure information, melt flow index, and mixability rating for representative styrene diblock copolymers and styrene triblock copolymers measured as described in the above paragraphs. Figure 1 Photograph of a sample forming a ribbon on a rotating roller to assess mixing ability.

[0197] Table 1

[0198]

[0199] As shown in Table 1 and Figure 1 As shown in the results, it can be clearly seen that the diblock samples (SEB-5, SEP-1, (S / EB)-EB-2, and EEPS-1) all mix well and form clear bands on the rotating roller. SEBS-2 has a comparable polymer structure and weight average molecular weight to SEB-5, except that it is a triblock copolymer, but SEBS-2 is difficult to mix in the roll mill, and SEBS-2 forms an opaque band on the rotating roller. Unexpectedly, as shown by the MFI values, SEP-1 and EEPS-1, which have higher Mw and higher melt viscosity, can both mix well. For example, SEP-1 has an Mw of 121,000. In contrast, SEPS-1, with an Mw of 95,000, is difficult to mix in the roll mill, and forms an opaque band on the rotating roller. The hard block of (S / EB)-EB-2, a copolymer of styrene and butadiene in a weight ratio of 9 / 1, performed best in the roll mixing evaluation, forming a very smooth, clear tape on the roll mill.

[0200] Tables 2a and 2b below list the mechanical properties of SEB-5 and SEBS-2 before and after curing with 0.5 phr of BIPB peroxide.

[0201] Table 2a

[0202]

[0203] As shown in the results of Table 2a, as a diblock copolymer, SEB-5 has very poor mechanical strength, breaking at less than 40% elongation. After crosslinking, SEB-5 is transformed into a stronger resin in the TPE class. For example, the hardness increases from 44 Shore A to 58 Shore A. Surprisingly, peroxide crosslinked SEBS-2 shows the opposite result. No enhancement in mechanical strength is observed for peroxide crosslinked SEBS-2. In fact, both hardness and tensile properties decrease slightly after crosslinking. In this table, phr is the unit abbreviation for parts per hundred of rubber or resin.

[0204] Table 2b

[0205]

[0206] As shown in Table 2b, diblock SEB-5 crosslinked with 0.5 parts of BIPB has a higher MH-ML compared to triblock SEBS-2. This result shows that SEB-5 can achieve a higher degree of crosslinking than SEBS-2 with a similar polymer structure. From the effect of peroxide crosslinking on mechanical properties and crosslinking kinetics, the diblock structure of SEB-5 is preferred in peroxide crosslinking.

[0207] In the following examples (abbreviated as Ex) and comparative examples (abbreviated as Comp Ex), a styrene block copolymer is mixed with an organic peroxide and a blowing agent to prepare a crosslinked foam.

[0208] In Example 1, SEB-1 hydrogenated styrene-butadiene diblock copolymer, 0.5 phr bis(1-(tert-butylperoxy)-1-methylethyl)-benzene (BIPB) as an organic peroxide, 3.0 phr azodicarbonamide (AC) as a foaming agent, 10 phr calcium carbonate, 1 phr zinc oxide and 1 phr stearic acid were mixed and kneaded in a roll mill at a roll surface temperature of 120° C. for 10 minutes, and then the mixture was molded into a sheet shape. The added amounts of BIPB, AC, calcium carbonate, zinc oxide and stearic acid were based on the total weight of the resin component (SEB-1 here).

[0209] The obtained sheet was filled into a die and then heated at 175°C and 100 kgf / cm 2 The cross-linked foam was obtained by heating under pressure of about 10 minutes. The size of the die was 10 mm thick, 150 mm long and 150 mm wide. Subsequently, the properties of the foam were measured according to the above method. The results are shown in Table 3 below.

[0210] Examples 2 to 5 were prepared and tested in the same manner as Example 1, except that different types of styrene diblock copolymers and different peroxide and blowing agent contents were used, as shown in Table 3 below. Comparative Example 1 was prepared and tested in the same manner as Example 1, except that partially hydrogenated SEBS-1 was used. The results are shown in Table 3 below.

[0211] Table 3

[0212]

[0213] As shown in the results of Table 3, the cross-linked foams of Examples 1 to 5 show that hydrogenated styrene-butadiene diblock copolymers with different molecular weights, 1,2-vinyl content, hydrogenation degree and styrene content in SEB diblock copolymers can be well mixed and foamed into lightweight foams with excellent impact resilience. For example, in Example 2, SEB-2 with a Mw of 75,000 can be well mixed to form a lightweight foam. SEBS-1 in Comparative Example 1 has a polymer structure comparable to that of SEB-1 in terms of polymer Mw, 1,2-vinyl content, hydrogenation degree and polystyrene content. Compared with Example 1, Comparative Example 1 has slightly better impact resilience, but poor tear resistance and compression set.

[0214] In the following examples, styrene block copolymers and ethylene copolymers were mixed with organic peroxides and blowing agents to prepare crosslinked foams. In the examples and comparative examples listed in Tables 4 to 7 below, the preparation and testing of the crosslinked foams were performed using the same method as in Example 1, except for different polymer formulations.

[0215] Table 4

[0216]

[0217] According to Table 4, Comparative Example 2 and Comparative Example 4 are EVA-1 and EVA-2, respectively. Example 6 and Example 7 are blends of SEB-1 diblock copolymer with EVA-1 and EVA-2, respectively. Comparative Example 3 and Comparative Example 5 are blends of SEBS-1 triblock copolymer with EVA-1 and EVA-2, respectively.

[0218] The results in Table 4 show that the EVA blended foams of Example 6, Comparative Example 3, Example 7 and Comparative Example 5 all show impact resilience better than Comparative Example 2 and Comparative Example 4. The foamed samples of Example 6 and Example 7 show foaming properties comparable to those of Comparative Examples 3 and 5.

[0219] Table 5

[0220]

[0221] Table 5 further shows the foaming mechanical properties of Examples 8 to 13 of different SEB diblock blends with EVA-1, Examples 14 and 15 of different (S / EB)-EB diblock blends with EVA-1 (wherein the hard block is a copolymer of styrene and butadiene), and Comparative Examples 6 and 7 of different SEBS triblock copolymer blends with EVA-1. SEBS-1 in Comparative Example 6 and SEBS-2 in Comparative Example 7 have polymer structures comparable to SEB-1 in Example 8 and SEB-5 in Example 12, respectively.

[0222] The results in Table 5 show that the foamed samples of styrene diblock copolymers of different polymer structures and molecular weights of Examples 8 to 15 all exhibit ideal impact resistance. In contrast, Example 8 and Comparative Example 6, as well as Example 12 and Comparative Example 7, respectively, exhibit comparable foaming properties.

[0223] Table 6

[0224]

[0225] Table 6 further shows the mechanical properties of the foams of Examples 16 to 19, which are blends of SEB-1 diblock with ethylene / 1-butene copolymer (POE-2), a mixture of EVA-1 and POE-2, ethylene / 1-octene copolymer (POE-1), and a mixture of EVA-1 and POE-1, respectively. The foam properties in Table 6 show that the SEB-1 diblock copolymer has excellent compatibility with ethylene copolymers of EVA and ethylene / α-olefin copolymers.

[0226] Table 7

[0227]

[0228] The crosslinked foams of Examples 20 to 25 were prepared and tested in the same manner as Example 1, except for the different polymer formulations. Examples 20 and 21 were SEP-1 (partially hydrogenated styrene-isoprene diblock copolymer) and a blend of SEP-1 and EVA-1, respectively. Examples 22 and 23 were SEP-2 (partially hydrogenated styrene-isoprene diblock copolymer with lower styrene content) and a blend of SEP-2 and EVA-1, respectively. Examples 24 and 25 were EEPS-1 (partially hydrogenated (butadiene / isoprene)-styrene diblock copolymer) and a blend of EEPS-1 and EVA-1, respectively. The foaming properties are shown in Table 7. Surprisingly, despite having high Mw and high melt viscosity, the compositions containing SEP-1, SEP-2 or EEPS-1 diblock copolymers were well mixed and foamed into lightweight foams.

[0229] In summary, the crosslinked foam obtained from the crosslinkable foam composition comprising the hydrogenated styrene diblock copolymer of the present invention shows excellent balanced mechanical properties, such as long-term durability, delamination tear strength, impact resilience, molding stability and operability. Therefore, the crosslinked foam obtained from the crosslinkable foam composition comprising the hydrogenated styrene diblock copolymer of the present invention can be suitably used in various molded products, such as shoe midsoles and outsoles, automotive parts, civil engineering and construction applications, household appliance parts, sporting goods, and a wide range of other fields.

[0230] Although the present invention provides relevant embodiments, it should be understood that many other possible modifications and variations may be made without departing from the spirit and scope of the present disclosure as hereinafter claimed.

Claims

1. A cross-linkable foaming composition comprising a hydrogenated styrene diblock copolymer, a free radical initiator and a foaming agent, characterized in that: The hydrogenated styrene diblock copolymer comprises: a first block comprising a conjugated diene monomer unit; and a second block comprising a styrene unit; wherein the hydrogenated styrene diblock copolymer comprises 10 to 60 wt % of the styrene units, 50 mol % or more of the conjugated diene monomer units are hydrogenated, and the weight average molecular weight of the hydrogenated styrene diblock copolymer is between 30,000 and 200,000; The free radical initiator is an organic peroxide, and the amount of the free radical initiator used is 0.01 to 10 wt % based on the total weight of the cross-linkable foaming composition; the organic peroxide is selected from the group consisting of diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, bis(1-(tert-butylperoxy)-1-methylethyl)-benzene, and combinations thereof; The foaming agent is a chemical foaming agent, and the amount of the foaming agent used is 0.5 to 10 wt % based on the total weight of the cross-linkable foaming composition; wherein the chemical foaming agent is an organic foaming agent, sodium bicarbonate, ammonium carbonate or a combination thereof, and the organic foaming agent is azodicarbonamide, bis(1-(tert-butylperoxy)-1-methylethyl)-benzene, 4,4'-oxybis(benzenesulfonylhydrazide), p-toluenesulfonylsemicarbazide, N,N'-dinitrosopentamethylenetetramine, diphenylsulfone-3,3'-disulfonylhydrazide, trihydrazine triazine or a combination thereof; The first block is a polymer block of a butadiene unit, an isoprene unit or a mixture thereof, and before hydrogenation, the 1,2-vinyl bond content of the butadiene unit is between 5 and 60 mol%, and before hydrogenation, the 3,4-vinyl bond content of the isoprene unit is between 5 and 60 mol%.

2. The cross-linkable foaming composition according to claim 1, characterized in that: The second block is a polymer block of styrene units.

3. The cross-linkable foaming composition according to claim 1, characterized in that: The second block is a polymer block of the styrene unit and a conjugated diene monomer unit, wherein the conjugated diene monomer unit is a butadiene unit, an isoprene unit or a mixture thereof, and the content of the conjugated diene monomer unit in the second block is less than or equal to 15 wt % of the total weight of the second block.

4. The cross-linkable foaming composition according to claim 1, characterized in that: The first block is a polymer block of butadiene units, and the second block is a polymer block of styrene units.

5. The cross-linkable foaming composition according to claim 1, characterized in that: The first block is a polymer block of a butadiene unit, and the second block is a polymer block of the styrene unit and a butadiene unit, wherein the content of the butadiene unit in the second block accounts for less than or equal to 15 wt % of the total weight of the second block.

6. The cross-linkable foaming composition according to claim 1, characterized in that: After hydrogenation, 60 to 95 mol % of the conjugated diene monomer units are hydrogenated.

7. The cross-linkable foaming composition according to claim 1, characterized in that: The organic peroxide is selected from the group consisting of dicumyl peroxide, bis(1-(tert-butylperoxy)-1-methylethyl)-benzene and mixtures thereof.

8. The cross-linkable foaming composition according to claim 1, characterized in that: The chemical blowing agent is azodicarbonamide.

9. The cross-linkable foaming composition according to claim 1, characterized in that: A cross-linking aid is also included.

10. A cross-linkable foaming composition according to claim 1, characterized in that: Also included is an ethylene copolymer, wherein the weight ratio of the ethylene copolymer to the hydrogenated styrene diblock copolymer is between 50 / 50 and 95 / 5.

11. The cross-linkable foaming composition according to claim 10, characterized in that: The ethylene copolymer includes ethylene-vinyl acetate copolymer, ethylene-α-olefin copolymer or a combination thereof.

12. The cross-linkable foaming composition according to claim 10, characterized in that: The ethylene copolymer is an ethylene-vinyl acetate copolymer, and the content of vinyl acetate accounts for 15 to 40 wt % of the total weight of the ethylene copolymer.

13. The cross-linkable foaming composition according to claim 10, characterized in that: A cross-linking aid is also included.

14. A foam, characterized in that: The cross-linkable foaming composition according to claim 1 is cross-linked and foamed.

15. The foam according to claim 14, characterized in that The specific gravity of the foam is 0.05 to 0.5 g / cm 3 , compression set rate is 30 to 65%, hardness is 20 to 80, and impact resilience is 40 to 80%; The hardness is measured according to ASTM D2240; The compression set rate is measured according to the following method: the foam is punched into a circle with a diameter of 2.54 cm, used as a test piece and compressed to a thickness of 50%; after keeping at 50°C for 6 hours, the pressure is released and the thickness is measured after 1 hour; and the magnitude of the residual deformation is evaluated.

16. The foam according to claim 14, characterized in that The specific gravity of the foam is 0.05 to 0.5 g / cm 3 , compression set rate is 30 to 65%, hardness is 20 to 80, and impact resilience is 55 to 80%; The hardness is measured according to ASTM D2240; The compression set rate is measured according to the following method: the foam is punched into a circle with a diameter of 2.54 cm, used as a test piece and compressed to a thickness of 50%; after keeping at 50°C for 6 hours, the pressure is released and the thickness is measured after 1 hour; and the magnitude of the residual deformation is evaluated.

17. The foam according to claim 14, characterized in that It is a footwear component.

18. The foam according to claim 14, characterized in that It is a midsole of a shoe.

19. A foam, characterized in that: The cross-linkable foaming composition according to claim 10 is cross-linked and foamed.

20. The foam according to claim 19, characterized in that The specific gravity of the foam is 0.05 to 0.4 g / cm 3 , compression set rate is 30 to 65%, hardness is 30 to 70, and impact resilience is 40 to 80%; The hardness is measured according to ASTM D2240; The compression set rate is measured according to the following method: the foam is punched into a circle with a diameter of 2.54 cm, used as a test piece and compressed to a thickness of 50%; after keeping at 50°C for 6 hours, the pressure is released and the thickness is measured after 1 hour; and the magnitude of the residual deformation is evaluated.

21. The foam according to claim 19, characterized in that The specific gravity of the foam is 0.05 to 0.4 g / cm 3 , compression set rate is 30 to 65%, hardness is 30 to 70, and impact resilience is 50 to 80%; The hardness is measured according to ASTM D2240; The compression set rate is measured according to the following method: the foam is punched into a circle with a diameter of 2.54 cm, used as a test piece and compressed to a thickness of 50%; after keeping at 50°C for 6 hours, the pressure is released and the thickness is measured after 1 hour; and the magnitude of the residual deformation is evaluated.

22. The foam according to claim 19, characterized in that It is a footwear component.

23. The foam according to claim 19, characterized in that It is a midsole of a shoe.

24. A foaming composition comprising a hydrogenated styrene diblock copolymer, characterized in that: The hydrogenated styrene diblock copolymer comprises: a first block comprising a conjugated diene monomer unit; and a second block comprising a styrene unit; wherein the hydrogenated styrene diblock copolymer comprises 10 to 60 wt % of the styrene units, 50 mol % or more of the conjugated diene monomer units are hydrogenated, and the weight average molecular weight of the hydrogenated styrene diblock copolymer is between 30,000 and 200,000; The first block is a polymer block of a butadiene unit, an isoprene unit or a mixture thereof, and before hydrogenation, the 1,2-vinyl bond content of the butadiene unit is between 5 and 60 mol%, and before hydrogenation, the 3,4-vinyl bond content of the isoprene unit is between 5 and 60 mol%.

25. The composition according to claim 24, characterized in that Also included are ethylene copolymers.

26. A use of the composition according to claim 24, characterized in that: Used to prepare a foam.

Citation Information

Patent Citations

  • Process for producing foams based on thermoplastic polyurethanes

    EP3259306A1

  • Partially hydrogenated block copolymers

    US3595942A

  • Selectively hydrogenated block copolymers

    US3700633A

  • Vulcanizable selectively hydogenated block copolymer compositions

    US3823203A

  • Cross-linked ethylenic polymer foam structures and process for making

    US5407965A